Pengaruh Kualitas Layanan Antar Jemput Dan Penanganan Komplain Terhadap Kepuasan Nasabah Produk Tabungan PT. BPRS Lantabur Tebu Ireng Sidoarjo - Jeni Devi Anjelina; Masruchin Masruchin (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the effect of service quality and complaint handling on customer satisfaction. This research uses quantitative methods. The sampling technique used is probability sampling technique. The sample in this study were customers who used shuttle services at BPRS Lantabur Tebu Ireng Sidoarjo with a total of 100 respondents. The results of this study were obtained from distributing questionnaires which were then processed using SPSS software version 20 which showed that the quality of shuttle services on customer satisfaction resulted in a significance value of 0.000 ≤ 0.05 which means that the quality of shuttle services has a positive effect on customer satisfaction. Meanwhile, the complaint handling variable shows a significance value of 0.001 ≤ 0.05, which means that the complaint handling variable has a positive effect on customer satisfaction. Then the quality of shuttle services and complaint handling simultaneously also affect customer satisfaction with a significance value of 0.000 ≤ 0.05.